Public faith in action : how to think carefully, engage wisely, and vote with integrity - Volf, Miroslav; McAnnally-Linz, Ryan (Grand Rapids, Michigan : Brazos Press, 2016)
Christian citizens have a responsibility to make political and ethical judgments in light of their faith and to participate in the public lives of their communities -- from their local neighborhoods to the national scene. But it can be difficult to discern who to vote for, which policies to support, and how to respond to the social and cultural trends of our time. This nonpartisan handbook offers Christians practical guidance for thinking through complicated public issues and faithfully following Jesus as citizens of their countries. The book focuses on enduring Christian commitments that should guide readers in their judgments and encourages legitimate debate among Christians over how to live out core values. The book also includes lists of resources for further reflection in each chapter and "room for debate" questions to consider.
Christ the center and norm -- Christ, the spirit, and flourishing -- Reading in contexts -- Wealth -- The environment -- Education -- Work and rest -- Poverty -- Borrowing and lending -- Marriage and family -- New life -- Health and sickness -- Aging life -- Ending life -- Migration -- Policing -- Punishment -- War -- Torture -- Freedom of religion (and irreligion) -- Courage -- Humility -- Justice -- Respect -- Compassion.
Includes index.
Includes bibliographical references (pages 219-236) and index.
Keywords: Christianity and politics; Christians -- Political activity; Church and social problems